2022
DOI: 10.1038/s41598-022-15012-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of the triglyceride-glucose index with weight-adjusted appendicular lean mass in Chinese adolescents aged 12–18 years old

Abstract: There is no study exploring the association between triglyceride-glucose (TyG) index and skeletal muscle mass in Chinese adolescents. Therefore, the objective of this study is to explore the association between TyG index and appendicular lean mass (ALM) in Chinese adolescents. In this study, 1336 adolescents (805 boys, 60.25%) aged 12–18 years in China were randomly selected through a stratified cluster sampling. According to the tertiles of TyG index, we separated all participants into three groups, and LM wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Ahn et al reported that higher TyG index values were found to be associated with an increased risk of low skeletal muscle mass index in Korean adults [ 20 ]. Other studies also showed that elevated levels of TyG index are a risk factor for reduced muscle mass or strength [ 21 , 22 ], even in adolescents between the ages of 12 and 18 [ 36 ]. In addition to evidence from cross-sectional studies, post hoc analyses of a prospective study suggested that baseline lower handgrip strength levels were inversely associated with the three-year follow-up TyG index values, which indicate that handgrip strength can be a predictor of future insulin resistance [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ahn et al reported that higher TyG index values were found to be associated with an increased risk of low skeletal muscle mass index in Korean adults [ 20 ]. Other studies also showed that elevated levels of TyG index are a risk factor for reduced muscle mass or strength [ 21 , 22 ], even in adolescents between the ages of 12 and 18 [ 36 ]. In addition to evidence from cross-sectional studies, post hoc analyses of a prospective study suggested that baseline lower handgrip strength levels were inversely associated with the three-year follow-up TyG index values, which indicate that handgrip strength can be a predictor of future insulin resistance [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The loss of muscle mass or strength and the development of chronic diseases, such as CVD and cognitive impairment, are the main contributors to frailty in older people. The TyG index has been reported to be positively related to sarcopenia, in populations with hypertension or without DM, as well as in adolescents or older people [21,[41][42][43]. Moreover, an elevated TyG index has been suggested to lead to elevated risk of CVD and mortality in cross-sectional or prospective studies [44][45][46].…”
Section: Discussionmentioning
confidence: 99%